Sinergisitas Gereja dan Influencer Rohani dalam Pemulihan Gambar Diri Native Digital - Joni Manumpak Parulian Gultom (Jurnal Teologi Berita Hidup, 2023)
Digital natives face self-image problems due to the development of social media. They consider themselves spiritual but not spiritual and are not interested in the church. A foul value system, as well as “Godless”, immoral, unethical, violent, and disparaging content of religion, are spreading without a hitch. All of these things started at a young age. If not answered immediately, this generation can be lost from moral civilization and the correct self-image. So the question arises, what form of synergy is there between the church and spiritual influencers in restoring a native digital self-image? What concrete steps should be? And what is the form of a Biblical native digital self-image? The purpose of this study,[1] is to explain synergies between churches and Christian influencers in the recovery of digital natives. [2] to describe the steps to the restoration of the self-image of this digital generation. [3] Explaining the native digital self-image according to Bible. Church research arguments and spiritual influencers play a role in restoring the native digital self-image. It is by optimizing the synergistic character of the church and synergistic spiritual influencers based on the Bible. The construction of the approach used in maximizing the existing synergies, namely by [1] self-image restoration missions as the basis of spiritual service, [2] spiritual influencer acting as extensions of church services, and [3] methods that focus on transformation, actions to accommodate growth and evangelism. Descriptive qualitative research method with literature study. The practical contribution of expanding church services, stimulating the birth of spiritual influencers, and creating sustainable synergies.